Ideology and ambivalence in Japanese discourses on business globalization. Issue 1 (2nd January 2017) - Macpherson, Iain
ABSTRACT: Neoliberalism's subjective dimensions – what Foucault decades ago loosely conceptualized as the 'entrepreneurial self' (1978–1979/2008) – have only recently been empirically studied. Such work remains sparse, and moreover lacking in global contexts, mostly examining western selves in western societies. This article attempts accordingly to advance understanding of neoliberalism through discourse analysis of how the ideology is affirmed and/or rejected by Japanese 'salarymen' discussing work and business in Japan. Three interview analyses illuminate the successes and struggles of neoliberal inculcation in the less native soil of Japan, where management and political economy are less committed to free market principles than in the 'Anglo-American' sphere. Analysis is divided into three sections, each exploring the predominant orientation which respondents articulate toward Japan's neoliberalization: affirmation, ambivalence, and neoliberalism qua neoconservatism. Attention is focused on the uncertainties, inconsistencies, or ironies participants explicitly or implicitly voice – for example, neoconservative sentiments ostensibly rejecting 'Americanization' yet aligning with neoliberal work intensification; or the simultaneous advocacy of neoliberalism and progressive, social liberalization. Examining such ideological entwinement or entanglement aids in mapping neoliberalism's variegated contours in Japan. At the same time, this intercultural examination identifies rhetorical pressure points extant in any socio-cultural sphere, upon which to focus counter-claims against neoliberalism.